Effectiveness of Open Selection of Pratama High Leadership Positions (JPT) Through The Merit System of The DIY Provincial Government During The Covid-19 Pandemic - Rizky Dwi Kusuma; Muhammad Eko Atmojo; Dyah Mutiarin (JIP (Jurnal Ilmu Pemerintahan) : Kajian Ilmu Pemerintahan dan Politik Daerah, 2022)
This study aims to analyze the effectiveness of the implementation of the 2020 DIY Primary JPT open selection which was carried out during the Covid-19 Pandemic conditions and what factors affect the effectiveness of the selection implementation. This needs to be done considering that open selection through the merit system is one way to create qualified, competent and professional human resources to run the government and realize the country's goals. DIY is also an area with good value in the implementation of the merit system needs to maintain this value so that the implementation of open selection can still run well, so there need to be adjustments to the selection processes given the limitations of activities during the pandemic. Research is conducted using descriptive qualitative research methods and data obtained from interview results and documentation. The results showed that the implementation of the 2020 DIY Primary JPT Open Selection consisting of selection announcements, administrative selection, competency tests (assessment centers), paper writing, idea/interview tests, and announcements of final results has been effective by the implementation planning and also pays attention to the provisions and regulations related to the Covid-19 Pandemic. The effectiveness of the implementation of open selection is influenced by three main factors, namely transparency, accountability, and infrastructure and technology.